Neurological soft signs and structural network changes: a longitudinal analysis in first-episode schizophrenia - Kong, Li; Herold, Christina; Bachmann, Silke; Schröder, Johannes (BMC psychiatry, 2023)
Neurological soft signs, Schizophrenia, Network, Longitudinal analysis